2020
DOI: 10.1182/bloodadvances.2019001346
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-based screens uncover determinants of immunotherapy response in multiple myeloma

Abstract: Cancer cells commonly develop resistance to immunotherapy by loss of antigen expression. Combinatorial treatments that increase levels of the target antigen on the surface of cancer cells have the potential to restore efficacy to immunotherapy. Here, we use our CRISPR interference– and CRISPR activation–based functional genomics platform to systematically identify pathways controlling cell surface expression of the multiple myeloma immunotherapy antigen B-cell maturation antigen (BCMA). We discovered that phar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 41 publications
2
24
2
Order By: Relevance
“…This functional genomic study suggests that regulation of surface CD38 largely occurs at the transcriptional, as opposed to protein trafficking, level. This finding was in sharp contrast to our prior CRISPRi results with BCMA, where we found that post-transcriptional mechanisms, such as proteolytic cleavage by γ-secretase and protein trafficking via the SEC61 translocon, played some of the strongest roles in determining surface BCMA levels 17 .…”
Section: Our Initialcontrasting
confidence: 99%
See 1 more Smart Citation
“…This functional genomic study suggests that regulation of surface CD38 largely occurs at the transcriptional, as opposed to protein trafficking, level. This finding was in sharp contrast to our prior CRISPRi results with BCMA, where we found that post-transcriptional mechanisms, such as proteolytic cleavage by γ-secretase and protein trafficking via the SEC61 translocon, played some of the strongest roles in determining surface BCMA levels 17 .…”
Section: Our Initialcontrasting
confidence: 99%
“…We specifically employed genome-wide screening with CRISPR interference (CRISPRi), an approach which leads to much higher specificity of knockdown than shRNA while avoiding potential toxicity of double-strand breakage with CRISPR deletion 26 . We recently used this approach to characterize regulators of surface B-cell Maturation Antigen (BCMA) in myeloma 17 . Here, we employed an RPMI-8226 cell line with the dCas9-KRAB machinery, required for CRISPRi, as described previously 17 .…”
Section: A Crispr Interference-based Screen Reveals Regulators Of Cd38 Surface Expressionmentioning
confidence: 99%
“…[5] Following an early report on an amanitin-antibody conjugate against Thy 1.2 antigen towards T lymphoma S49.1 cells, [6] Moldenhauer et al demonstrated the extraordinary promise of α-amanitin as a payload for ADC development; an anti-EpCAM antibody-amanitin conjugate remarkably cured 60 % (3 of 5) mice with pancreatic tumor xenografts, [7] paving the way for HDP-101, an amanitinbased ADC for the treatment of multiple myeloma and the first amanitin-based ADC that is advancing towards clinical trials. [8] Others have explored targeted amanitin conjugates underscoring interest in amanitin and its chemistry. [9] With this interest in using α-amanitin for therapeutic applications, new knowledge as to the molecular basis of toxicity will be essential for designing new toxicophores for therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, CRISPR interference and CRISPR activation were used to identify genes that led to increase in BCMA on the MM cell surface. They discovered that the knockdown of HDAC7 and SEC61A (part of SEC61 complex) increased the levels of BCMA (Ramkumar et al, 2020). They then verified their results by using drugs to inhibit HDACs protein and the Sec61 complex, whereby an increase in BCMA levels was observed.…”
Section: Application Of Various Crispr Systems In Functional Genomics Of Other Hematological Malignanciesmentioning
confidence: 90%